Do we use standards? The presence of ISO/TC-46 standards in the scientific literature (2000-2011) - Matysek, Anna (Qualitative and Quantitative Methods in Libraries; Vol 2 No 1 (2013): March 2013 Issue, 2017)
The paper presents the results of research on the presence of ISO/TC-46 "Information and documentation" standards in the scientific literature between 2000 and 2011. During this period the Committee has published nearly 50 standards in the field of library and information science. The first part of the study covers articles on ISO standards. The survey was based on the abstracting databases in the field of library and information science - Library and Information Science Abstracts (LISA) and Library, Information Science & Technology Abstracts (LISTA). The second part is an analysis of ISO standards citations in citation databases. The results indicate which standards receive the biggest attention - and thus are needed by librarians, and which documents are ignored. An analysis of articles topics and citations illustrates the level of interest in the ISO standardization work in the scientific literature.